Imaginal and Virtual Reality-based Public Speaking Practice for Communicating with Intercultural Audiences - Brunotte, Josh; Takai, Jiro (Intercultural Communication Studies, 2026)
Imaginal and Virtual Reality-based Public Speaking Practice for Communicating with Intercultural Audiences